The Existence of Islamic Young Journalist Alliance in Increasing Literacy Competencies in Al-Amien University Prenduan Students - Uswatun Hasanah; Miftahul Jannah (Saniya Institute, 2025)
Literacy is a fundamental skill in education, encompassing not only reading and writing but also critical thinking, analysis, and deep comprehension of information. At Al-Amien University (UNIA) Prenduan, the Student Activity Unit (UKM) AJMI serves as a platform for female students passionate about writing and journalism. Despite high enthusiasm for this organization, the development of students' literacy competencies remains suboptimal. This study aims to analyze the role of UKM AJMI in enhancing female students' literacy skills and identify the challenges hindering its implementation. Adopting a descriptive qualitative approach and Edward III’s policy implementation theory, the study evaluates four key factors: communication, resources, disposition, and bureaucratic structure. Data were gathered through interviews, observations, and documentation involving UKM AJMI administrators and members. Findings reveal that UKM AJMI has initiated programs such as journalism training, book discussions, publication opportunities, and digital literacy workshops to bolster students' literacy. However, implementation faces obstacles, including poor internal coordination, limited resources (funding and access to reading materials), low member discipline and participation, and difficulties in forging external partnerships. To address these issues, the study recommends strengthening organizational coordination, optimizing resource allocation, and expanding collaboration with external institutions to foster more effective literacy development. This research serves as a valuable reference for designing university-level literacy programs and encourages further studies in this field.